Nodal dynamic charging price formulation for electric vehicle through the Stackelberg game considering grid congestion. Issue 5 (22nd March 2021) - Zhang, Qian; Sun, Tao; Ding, Zhuwei; Li, Chunyan
Abstract: The disordered charging of electric vehicles (EVs) may result in transmission congestion during the peak load period; therefore, a nodal dynamic charging price (NDCP) strategy is proposed to schedule the charging activity of regional electric vehicle agents (REVAs) to manage congestion. REVA is responsible for meeting the charging demand of users at a minimum charging cost, while the grid aims at minimising the congestion management cost and regulates the charging price of different nodes. The Stackelberg game theory is used to model the negotiation process of charging price, and the congestion contribution index is proposed to determine the congestion cost that the user side should be allocated. The proposed approach is implemented on a modified IEEE 30 bus system, and the results show that the congestion caused by EVs is reduced effectively, while the charging cost and congestion cost are also optimised.